THE EFFECT OF APPLYING GREEN TARGET COST ON FINANCIAL PERFORMANCE IN KUFA CEMENT FACTORY: APPLIED STUDY - Hawraa Abed Alameer Ahmed (Scholar Express Journals, 2025)
The research aims to show the impact of applying the green target cost, which is considered one of the modern costing techniques and the role it can play on the financial performance measured by a number of indicators, by applying it in the Iraqi General Cement Company, represented by the Kufa Cement Factory, as the subject of research. The practical analysis was carried out using a set of statistical tools that suit the objectives of the research, and the hypotheses were tested using SPSS software. The research has reached many conclusions in the theoretical and applied fields, the most important of which are: that the application of the green target cost contributes to the explanation of 44.8% of the changes in the financial performance of the Kufa Cement Factory, while the remaining percentage is due to other factors outside the scope of the current research, confirming that this technology has an important impact but is not the only determinant of financial performance. The research provided a set of recommendations, most notably: It is necessary to pay attention to the application of the green target cost to include all stages of production processes in the plant, while working to improve other supporting factors such as raising operational efficiency and rationalizing the use of resources, in order to enhance the impact of this technology on achieving sustainable financial performance.
Keywords: Target Cost; Financial Performance; Performance Efficiency; Cement Factory